Bayi Dengan Sindrom Kornelia Babies With Cornellia Syndrom - Sulaiman (Medula, 2021)
Syndrome Cornelia de Lange is a multisystem developmental disorder is genetically heterogeneous, characterized by delayed growth and cognitive, upper limb disorders, gastroesophageal dysfunction, diaphragm, heart, eyes, palate, and genitourinary anomalies, hirsutism, and distinctive craniofacial picture. This case report conducted on August 21th till August 25th 2013 in Perinatology Unit of Abdul Moeloek Hospital Lampung. Female neonates, 3 days of ages, with the chief complaint of feeding problem, pouty mouth, moaning, hypoactive. History of 35 weeks gestasional age, spontaneous vaginal with the presentation of the head, and absence of grimace. Length 42 cm, Weight 1800 gr, head circumference 27 cm. On physical examination found microchepaly, hirsutism forehead, eyebrows synophrys, long eyelashes, small and upturned nose, long philtrum, and protrusion of the upper jaw, conjunctival pallor, palms smaller than the size of the arm, back hirsutism, substernal retraction, rugged ronkhi in both of lungs and a systolic murmur. Patients diagnosed with Syndrome Cornelia de Lange in clinical sepsis neonatorum and respiratory distress syndrome (RDS). Management by maintaining the temperature 36,50 -37,50 C, IVFD D10% 10 cc/h, O2 0.5 L/m, ceftazidime injection of 90 mg/12h, ampicillin 90 mg/12h, Gentamicin 4 mg/12h, 10.8 mg aminophylline loading, maintenance 4.5 mg/12h, Aminofusin 108 cc/day, 10% KCL 1,8cc/day drip in D10, 3% NaCl 7,2cc/day drip in D10, Ca gluconate 1, 8cc/day drip in D10, PRC transfusion 40 cc, OGT no.5. Management for Cornelia Syndrome needs multidisciplinary team approach for maximum outcome and prevent global development delay or even death.